Indoor concentrations of particulate matter 2.5 in a pediatric emergency service - Catiane Zanin Cabral; Alan da Silveira Fleck; Fernanda Chaves Amantéa; Claudia Ramos Rhoden; Sérgio Luis Amantéa
Abstract Objective: To evaluate air quality in the waiting room of a pediatric emergency service considering the serial concentrations of particulate matter (PM2.5), and to determine if the number of people present in the room can have an influence on the pollutant concentrations. Methods: Cross-sectional study, carried out in the waiting room of a reference pediatric hospital in the city of Porto Alegre, conducted in a one-year period, in a continuous-time sample including all of the four seasons of the year. The monitoring of PM2.5 was performed using a real-time aerosol monitor (DustTrak II). The number of people in the room was determined every hour and the climatic characteristics per daily mean. The concentration of PM2.5 and the number of people were expressed by mean and standard deviation. The means were compared by Analysis of Variance and Pearson's correlation coefficient. Results: There was a significant increase in the concentration of PM2.5 in the autumn, when compared to other seasons (p<0.001). The pollutant increase, in this season, was accompanied by the higher number of people in the emergency room (p=0.026). The association between PM2.5 and the number of people is confirmed by the positive correlation between these two variables (r=0.738; p<0.001). Conclusions: The pediatric emergency waiting room showed elevated PM2.5 in all seasons. The number of people in the room had a positive correlation with the concentration of the pollutant in the environment.